Is There a Connection Between Intestinal Barrier Disruption, Dysbiosis, and the Development of Type 2 Diabetes Mellitus? - a literature review - Wicha, Katarzyna; Brzozowska, Monika; Wardal, Wiktoria; Furlepa, Natalia; Rzenno, Robert; Wojciechowska, Karolina; Matuszewska, Marcelina; Sidz, Natalia; Tomaszewska, Magdalena; Jedlikowska, Wiktoria (Journal of Education, Health and Sport, 2025)
Introduction and purpose: The intestinal barrier and microbiota play an instrumental role in maintaining good health. Its proper function is ensured by many different mechanisms, especially intercellular tight junctions (TJ). Numerous factors such as poor eating habits may lead to dysbiosis, disruption of TJs and subsequently to the development of the leaky gut syndrome. Objecton: To assess whether there is a connection between intestinal barrier disruption, dysbiosis and higher probability of the development of type 2 diabetes mellitus (T2DM). Material and method: The review was conducted with the use of databases such as PubMed and Scopus. The used key words were as follows: intestinal barrier, gut microbiome, leaky gut syndrome, diabetes mellitus and hyperglycemia. Only studies which contained relevant information about the influence of an increased intestinal permeability and dysbiosis on diabetes mellitus were enrolled in this research. Results: DM may lead to increased intestinal permeability due to numerous mechanisms such as GLUT-2-dependent mechanisms, dysfunctions in tight junction, entrance of pathogenic bacteria into the circulation, which consequently may cause a low systemic inflammation and beta cell destruction. There is a distinct possibility that intestinal barrier may be restored with use of butyrate, prebiotics, antibiotics, GLP-2 agonists, probiotics, metformin, colostrum and kombucha. According to studies proper microflora may improve intestinal barrier’s function and also glucose management. conclusion: Taking into consideration all facts mentioned above, the authors drew a conclusion that there is a strong connection between intestinal barrier disruption, state of a microbiome and the development of T2DM.